Passive component as thermal capacitance and heat sink - Paolucci Milko; Standing Martin (2017)
Representative implementations of devices and techniques provide improved thermal performance of a chip die disposed within a layered printed circuit board (PCB). Passive components may be strategically located on one or more surfaces of the PCB. The passive components may be arranged to conduct heat generated by the chip die away from the chip die.